Polyethylene terephthalate resin film, polarizing plate using same, transparent conductive film, touch panel, and image display device
By controlling the physical parameters of the polyethylene terephthalate-based resin film, the fracture and convex edge problems during slitting processing are solved, and its application performance in image display devices is improved.
Patent Information
- Application Number
- CN202380036085.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-04-27
- Filing Date
- 2023-04-18
- Publication Date
- 2024-12-13
AI Technical Summary
The existing polyethylene terephthalate-based resin films are prone to breaking and produce convex edges and foreign matters during slitting and processing, which affects product quality and productivity.
By controlling the mesophase orientation parameters, delay amount, elastic modulus and fracture strength of the polyethylene terephthalate-based resin film, its stability and mechanical properties during slitting processing are ensured. Specific measures include adjusting the delay amount of the film in the range of 3000 to 30000 nm, the mesophase orientation parameter is above 0.275, the elastic modulus in the slow axis direction is below 8600MPa, the fracture strength is below 450MPa, and the film is optimized through heat treatment and tensile technology. structure.
It effectively suppresses the occurrence of fractures, convex edges and foreign matters during slitting processing, improves the processing adaptability and product quality of the film, and is suitable for polarizing plates, transparent conductive films, touch panels and liquid crystal display devices.
Smart Images

Figure BDA0005099811050000391 
Figure HDA0005099811060000011 
Figure HDA0005099811060000021
Abstract
Description
Technical Field
[0001] The present invention relates to a polyethylene terephthalate resin film, a polarizing plate using the same, a transparent conductive film, a touch panel, and an image display device such as a liquid crystal display device and an organic EL display device. Background Art
[0002] The polarizing plate used in a liquid crystal display (LCD) is usually composed of a polarizing plate dyed with iodine and sandwiched between two polarizing element protective films such as polyvinyl alcohol (PVA). As the polarizing element protective film, a triacetyl cellulose (TAC) film is usually used. In recent years, with the thinning of LCDs, the thinning of polarizing plates is required. However, if the thickness of the TAC film used as a protective film is reduced for this purpose, sufficient mechanical strength cannot be obtained, and the problem of deterioration of moisture permeability occurs. In addition, TAC film is very expensive, and polyester film has been proposed as a cheap alternative raw material (patent documents 1 to 3), but there is a problem of observing rainbow-shaped color spots.
[0003] When a birefringent oriented polyester film is disposed on one side of the polarizer, the polarization state of the linearly polarized light emitted from the backlight unit or the polarizer changes when passing through the polyester film. The transmitted light shows interference colors that are unique to the delay amount, which is the product of the birefringence and thickness of the oriented polyester film. Therefore, if a discontinuous emission spectrum such as a cold cathode tube or a hot cathode tube is used as a light source, different transmitted light intensities are displayed depending on the wavelength, forming rainbow-shaped color spots.
[0004] As a means to solve the above-mentioned problem, it is proposed to use a white light source having a continuous and wide-range emission spectrum such as a white light-emitting diode as a backlight source, and further use an oriented polyester film having a certain delay amount as a polarizer protective film (Patent Document 4). The white light-emitting diode has a continuous and wide-range emission spectrum in the visible light region. Therefore, if the envelope shape of the interference color spectrum caused by the transmitted light passing through the birefringent body is focused on, by controlling the delay amount of the oriented polyester film, a spectrum similar to the emission spectrum of the light source can be obtained, thereby suppressing rainbow spots.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2002-116320
[0008] Patent Document 2: Japanese Patent Application Publication No. 2004-219620
[0009] Patent Document 3: Japanese Patent Application Publication No. 2004-205773
[0010] Patent Document 4: WO2011 / 162198 Summary of the invention
[0011] Problem that the invention aims to solve
[0012] It is known that polyethylene terephthalate resin films that have been given a certain amount of delay in order to suppress rainbow spots are used in various applications such as polarizer protective films, substrates for transparent conductive films such as touch panels, and surface covering films. However, due to their high orientation anisotropy, they are prone to cracking in a direction parallel to the slow axis, and there is a possibility that the productivity will be reduced due to breakage during the slitting process. In addition, due to the increase in cutting resistance associated with oriented crystallization, the cutting portion is elongated during the slitting process, resulting in a convex edge at the end of the product roll, which sometimes damages the quality of the product. In addition, as the cutting resistance increases, the film is cut by the cutting portion, and the resulting fine powder becomes a foreign matter, which sometimes damages the quality of the product.
[0013] That is, the present invention aims to provide a polyethylene terephthalate resin film having excellent processing adaptability, in particular, being able to effectively suppress the generation of breakage or convex edges during slitting processing. Another object is to provide a polarizing plate, a transparent conductive film, a touch panel, and an image display device such as a liquid crystal display device and an organic EL display device using the polyethylene terephthalate resin film.
[0014] Solutions for solving problems
[0015] The present inventors conducted intensive research and found that, for a polyethylene terephthalate resin film having a specific range of retardation, the above-mentioned problems can be solved by controlling the intermediate phase orientation parameter of the polyethylene terephthalate resin film measured by the ATR-FTIR method to a value above a certain level, thereby completing the present invention.
[0016] Representative embodiments of the present invention are described below.
[0017] Item 1.
[0018] A polyethylene terephthalate resin film that satisfies the following (1) and (2).
[0019] (1) Polyethylene terephthalate resin films have a retardation of 3000 to 30000 nm
[0020] (2) The mesophase orientation parameter of the polyethylene terephthalate resin film measured by ATR-FTIR method and represented by the following formula is 0.275 or more
[0021] (mesophase orientation parameter) = R slow / R fast
[0022] Among them, R slow =(1457cm in the slow axis direction -1 absorbance at 795cm in the slow axis direction) / (absorbance at 795cm in the slow axis direction) -1 Absorbance at fast =(1457cm in the fast axis direction -1 Absorbance at 795cm) / (absorbance at 795cm -1 absorbance at ).
[0023] Item 2.
[0024] The polyethylene terephthalate-based resin film according to Item 1, further satisfying the following (3) and (4).
[0025] (3) Elastic modulus in the slow axis direction is 8600 MPa or less
[0026] (4) The ratio of the elastic modulus in the slow axis direction to the fast axis direction is 3.6 or less
[0027] Item 3.
[0028] The polyethylene terephthalate-based resin film according to item 1 or 2, further satisfying the following (5).
[0029] (5) The fracture strength in the slow axis direction is 450 MPa or less
[0030] Item 4.
[0031] The polyethylene terephthalate resin film according to any one of items 1 to 3, further satisfying the following (6).
[0032] (6) The rigid amorphous fraction represented by the following formula is 33% by mass or more
[0033] (Rigid amorphous fraction (mass %)) = 100 - (Flexible amorphous fraction (mass %)) - (Mass fraction crystallinity (mass %))
[0034] Item 5.
[0035] A polarizing plate comprising the polyethylene terephthalate resin film according to any one of items 1 to 4 laminated on at least one surface of a polarizer as a polarizer protective film.
[0036] Item 6.
[0037] An image display device comprising the polarizing plate described in item 5.
[0038] Item 7.
[0039] A liquid crystal display device comprises a backlight source, two polarizing plates, and a liquid crystal unit arranged between the two polarizing plates, wherein at least one of the two polarizing plates is the polarizing plate described in item 5.
[0040] Item 8.
[0041] An organic EL display device comprising the polarizing plate described in item 5.
[0042] Item 9.
[0043] A transparent conductive film comprising the polyethylene terephthalate resin film according to any one of items 1 to 4 as a base film of the transparent conductive film.
[0044] Item 10.
[0045] A touch panel comprising the transparent conductive film according to item 9.
[0046] Item 11.
[0047] An image display device comprising the polyethylene terephthalate resin film according to any one of items 1 to 4 as an anti-scattering film or a surface protection film on a viewing side of an image display panel.
[0048] Effects of the Invention
[0049] According to the present invention, a polyethylene terephthalate resin film having excellent processing adaptability and being particularly capable of effectively suppressing the generation of breakage, convex edges and foreign matter during slitting can be provided. In addition, a polarizing plate, a transparent conductive film, a touch panel, and an image display device such as a liquid crystal display device and an organic EL display device using the polyethylene terephthalate resin film can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] Figure 1 This is an example of determining the nominal stress-nominal strain curve for a tensile test.
[0051] Figure 2 This is an example of measuring the storage modulus by dynamic viscoelasticity measurement. DETAILED DESCRIPTION
[0052] 1. Polyethylene terephthalate resin film
[0053] The polyethylene terephthalate resin film of the present invention preferably has a retardation of 3000 nm or more and 30000 nm or less. If the retardation is 3000 nm or more, the generation of interference colors can be suppressed when observed from an oblique direction, ensuring good visibility. The preferred lower limit of the retardation is 4000 nm, and the further preferred lower limit is 5000 nm.
[0054] On the other hand, the upper limit of retardation is preferably 30000nm. Even if a polyethylene terephthalate resin film with more than retardation is used, further improvement of visibility cannot be obtained in fact, and the thickness of the film also becomes quite thick, and the operability as an industrial material is reduced. The preferred upper limit is 10000nm, the more preferred upper limit is 9000nm, and the further more preferred upper limit is 8000nm.
[0055] It should be noted that the refractive index difference in the film plane (refractive index in the slow axis direction - refractive index in the fast axis direction) is preferably 0.08 or more. Being strongly stretched in one direction, the film plane with a large refractive index difference can obtain sufficient delay even if it is a thinner film, which is preferred from the viewpoint of thin filmization, more preferably 0.09 or more, further preferably 0.10 or more, particularly preferably 0.105 or more, and most preferably 0.11 or more. The present invention is preferably applicable to such a film with a large refractive index difference. On the other hand, when the refractive index difference in the film plane is too large, the anisotropy of the mechanical properties of the film becomes significant, and therefore there is a tendency to easily produce cracks, ruptures, etc., and the above-mentioned refractive index difference is preferably 0.15 or less, more preferably 0.145 or less, further preferably 0.14 or less, further preferably 0.135 or less, particularly preferably 0.13, and most preferably 0.125 or less.
[0056] It should be noted that the retardation of the present invention can be obtained by measuring the refractive index in the biaxial direction of the film surface and the film thickness, or by using a commercially available automatic birefringence measuring device such as KOBRA-21ADH (Oji Scientific Instruments). The refractive index is measured at a wavelength of 589 nm.
[0057] In the polyethylene terephthalate resin film of the present invention, the mesophase orientation parameter, which is an index of the orientation degree of the oriented mesophase (mesophase) in the slow axis direction within the film surface, is 0.275 or more, which is preferred from the viewpoint of reducing the cutting resistance during cutting by suppressing excessive oriented crystallization, suppressing the generation of breakage, convex edges and foreign matter during slitting. The mesophase orientation parameter of the present invention is preferably 0.275 or more, more preferably 0.280 or more, further preferably 0.285 or more, and particularly preferably 0.290 or more. From the viewpoint of imparting good dimensional stability to the polyethylene terephthalate resin film by moderately carrying out oriented crystallization, the mesophase orientation parameter is preferably 0.500 or less, more preferably 0.450 or less, further preferably 0.400 or less, further preferably 0.370 or less, particularly preferably 0.360 or less, and most preferably 0.355 or less.
[0058] The mesophase orientation parameter of the polyethylene terephthalate-based resin film is represented by the following formula (1).
[0059] (mesophase orientation parameter) = R slow / R fast ···(1))
[0060] In the above formula (1), R slow =(1457cm in the slow axis direction -1 absorbance at 795cm in the slow axis direction) / (absorbance at 795cm in the slow axis direction) -1 Absorbance at fast =(1457cm in the fast axis direction -1 Absorbance at 795cm) / (absorbance at 795cm -1 1457cm -1 The absorbance at 795 cm -1 The absorbance at 1457 cm is determined by Fourier transform infrared spectroscopy (ATR-FTIR) based on total reflection measurement using a commercially available Fourier transform infrared spectrophotometer such as FTS 60A / 896 (Varian). In the infrared absorption spectrum of the polyethylene terephthalate resin film of the present invention, 1457 cm -1 The absorbance peak is at 1454 cm -1 The absorbance peak originating from the amorphous phase appears at 1463 cm -1 The absorbance peaks at 1457 cm-1 are caused by the overlap of the absorbance peaks of the mesophase (also called oriented mesophase, which is equivalent to the oriented amorphous phase as the precursor of the crystal). -1 The dichroic ratio of the absorbance peak at 1454 cm reflects the orientation anisotropy of the mesophase. -1 With 1463cm -1 The absorbance peaks at 1454 cm -1 The absorbance peak at 1463 cm corresponds to the combination of a gauche methylene group (relaxed state) and a trans ester bond (tightened state). -1 The absorbance peak at 795 cm corresponds to the combination of a trans-methylene group and a Pond's ester bond. -1 The absorbance at 1457cm reflects the out-of-plane vibration of the benzene ring. The absorbance does not change due to the orientation of the film surface or the pressure of the anvil during ATR measurement. Therefore, it can be used to standardize the absorbance at other wavenumbers. -1 The absorbance at 1457 cm is not necessarily -1 The absorbance at 1457 cm -1 Nearby (1452cm -1~1462cm -1 ) can be read as the absorbance of the peak observed at 1457 cm -1 Similarly, 795cm -1 The absorbance at 795 cm is not necessarily -1 The absorbance at 795 cm -1 Nearby (790cm -1 ~800cm -1 ) can be read at 795 cm -1 The details of the measuring method will be described later in the Examples.
[0061] Generally, the processing adaptability of polyethylene terephthalate resin films is affected by the crystals that grow in the orientation direction accompanying stretching. The polyethylene terephthalate resin film of the present invention improves the orientation anisotropy within the film surface for the purpose of suppressing rainbow spots, and the crystals grow preferentially in the slow axis direction corresponding to the main stretching direction. The growth of crystals increases the cutting resistance in the fast axis direction orthogonal to the slow axis direction, and makes the polyethylene terephthalate resin film brittle. For the above reasons, polyethylene terephthalate resin films formed by known methods sometimes produce fine powder caused by film wear and convex edges at the ends of the product rolls caused by the elongation of the film when the polyethylene terephthalate resin film is cut during the slitting process. The greater the refractive index difference, the more significant it is. The inventors of the present invention have conducted various studies and found that by controlling the intermediate phase orientation parameter, which is an indicator of the degree of amorphous orientation in the slow axis direction within the film surface, within the above-mentioned range, it is possible to effectively suppress the embrittlement of the polyethylene terephthalate resin film and the increase in cutting resistance even when the orientation anisotropy is increased, and it is possible to effectively suppress the generation of fine powder due to the cutting of the polyethylene terephthalate resin film in the cut part during the slitting process and the generation of convex edges at the ends of the product rolls due to the stretching of the film.
[0062] The present invention exhibits excellent effects when the slow axis direction is in the TD direction and is preferably applicable, but even when the slow axis direction is in the MD direction, the effect of suppressing the generation of ridges and fine powders is high and is also suitable when the slow axis direction is in the MD direction.
[0063] In order to further reduce the cutting resistance in the fast axis direction and further suppress the convex edge at the end of the product roll caused by the generation of fine powder or elongation of the film due to the cutting of the polyethylene terephthalate resin film in the slitting process, the elastic modulus of the polyethylene terephthalate resin film of the present invention in the slow axis direction within the film surface is preferably 8600 MPa or less. The elastic modulus of the polyethylene terephthalate resin film in the slow axis direction is preferably 8600 MPa or less, more preferably 8500 MPa or less, further preferably 8400 MPa or less, and particularly preferably 8300 MPa or less. The lower limit is not particularly limited, but from the perspective of maintaining sufficient orientation anisotropy to suppress rainbow spots, it is preferably 5400 MPa or more, more preferably 5450 MPa or more, further preferably 5500 MPa or more, and particularly preferably 5550 MPa or more.
[0064] In order to further reduce the cutting resistance in the fast axis direction and further suppress the generation of fine powder due to the cutting of the polyethylene terephthalate resin film in the slitting process or the convex edge at the end of the product roll due to the elongation of the film, the ratio of the elastic modulus in the slow axis direction to the fast axis direction of the polyethylene terephthalate resin film in the film surface of the present invention is preferably 3.6 or less. The ratio of the elastic modulus in the slow axis direction to the fast axis direction of the polyethylene terephthalate resin film is preferably 3.6 or less, more preferably 3.5 or less, further preferably 3.4 or less, and particularly preferably 3.3 or less. The lower limit is not particularly limited, but from the perspective of maintaining orientation anisotropy sufficient to suppress rainbow spots, it is preferably 2.0 or more, more preferably 2.5 or more, further preferably 2.6 or more, and particularly preferably 2.7 or more. In addition, the elastic modulus in the fast axis direction is preferably 2000 MPa or more, more preferably 2300 MPa or more, further preferably 2350 MPa or more, particularly preferably 2400 MPa or more, and most preferably 2450 MPa or more. The upper limit is preferably 4300 MPa or less, more preferably 4200 MPa or less, further preferably 4100 MPa or less, further preferably 4000 MPa or less, particularly preferably 3500 MPa or less, and most preferably 3000 MPa or less.
[0065] The value of the elastic modulus may vary greatly depending on the measurement method. Generally, the elastic modulus is defined as the slope of the stress-strain curve obtained by the tensile test at the initial stage of tension. In addition to the surface shape, pressing force, and preliminary force of the fixture used for measurement, the value of the elastic modulus also varies greatly depending on the strain range used to calculate the slope. For example, Figure 1The nominal stress-nominal strain curve shown (measured by the method according to JIS K7161 described later in the examples) shows that the elastic modulus is calculated to be 6986 MPa in the strain range (nominal strain: 0.0005 to 0.0025) according to Item 10.3.2 of JIS K7161, 6469 MPa in the nominal strain range of 0.0005 to 0.0100, 5149 MPa in the nominal strain range of 0.0005 to 0.0200, and 2590 MPa in the nominal strain range of 0.0005 to 0.0500. In addition, the elastic modulus may also be the value of the storage modulus obtained by dynamic viscoelasticity measurement, but the obtained value varies greatly depending on the measurement temperature. Figure 2 The dynamic viscoelasticity was measured by a dynamic viscoelasticity measuring device (DMS6100) manufactured by Seiko Instruments Inc. according to JIS-K7244. Figure 1 Temperature dependence of storage modulus of the same sample measured in (measurement conditions are tensile mode, drive frequency 1 Hz, chuck distance 5 mm, heating rate 2 ° C / min, measurement temperature range 20 ° C ~ 230 ° C). For example, the elastic modulus at 20 ° C is 6958 MPa, the elastic modulus at 60 ° C is 6425 MPa, the elastic modulus at 100 ° C is 4533 MPa, the elastic modulus at 140 ° C is 1028 MPa, the elastic modulus at 180 ° C is 719 MPa, and the elastic modulus at 220 ° C is 497 MPa. The average value of a specific range is usually adopted, for example, the average elastic modulus in the range of 20°C to 60°C is 6718MPa, the average elastic modulus in the range of 20°C to 100°C is 6244MPa, the average elastic modulus in the range of 20°C to 140°C is 4931MPa, the average elastic modulus in the range of 20°C to 180°C is 3930MPa, the average elastic modulus in the range of 20°C to 220°C is 3254MPa, and the average elastic modulus in the range of 100°C to 220°C is 1264MPa. As described above, the value obtained by the elastic modulus varies greatly depending on the measurement method, but the claims of the present invention are values measured by the method according to Item 10.3.2 of JIS K7161, and the details of the measurement method are described later in the Examples.
[0066] In order to further reduce the cutting resistance in the fast axis direction and further suppress the generation of fine powder due to the cutting of the polyethylene terephthalate resin film in the slitting process or the generation of convex edges at the ends of the product rolls caused by the elongation of the film, the polyethylene terephthalate resin film of the present invention preferably has a breaking strength in the slow axis direction within the film surface of 450 MPa or less. The breaking strength in the slow axis direction of the polyethylene terephthalate resin film is more preferably 440 MPa or less, further preferably 430 MPa or less, and particularly preferably 420 MPa or less. The lower limit is not particularly limited, but is preferably 220 MPa or more, more preferably 230 MPa or more, further preferably 240 MPa or more, and particularly preferably 250 MPa or more from the perspective of maintaining orientation anisotropy sufficient to suppress rainbow spots.
[0067] From the viewpoint of further suppressing the embrittlement of the polyethylene terephthalate resin film, further suppressing the fracture starting from the cut portion in the slitting process, and the generation of fine powder by cutting the polyethylene terephthalate resin film, the rigid amorphous fraction of the polyethylene terephthalate resin film of the present invention is preferably 33% by mass or more. The rigid amorphous fraction of the polyethylene terephthalate resin film is more preferably 34% by mass or more, more preferably 35% by mass or more, and particularly preferably 36% by mass or more. The upper limit is preferably 60% by mass, but 50% by mass or less or 45% by mass or less is also sufficient and is a more preferred range. Here, the rigid amorphous fraction is represented by the following formula (2).
[0068] (Rigid amorphous fraction (mass %)) = 100 - (Flexible amorphous fraction (mass %)) - (Mass fraction crystallinity (mass %)) ... (2))
[0069] In the past, it was believed that the higher-order structure of polymers was divided into crystals and amorphous. However, in recent years, the amorphous region can be further distinguished due to the temperature dependence of its molecular motion, and flexible amorphous in which the molecular motion is released at the glass transition temperature (Tg) and rigid amorphous in which the molecular motion is also frozen at a temperature above Tg have been reported. It is known that the rigid amorphous remains in an amorphous state until a temperature of about 200°C in the case of polyethylene terephthalate. It is generally believed that the rigid amorphous exists in the boundary region between the crystal and the flexible amorphous, and the rigid amorphous fraction increases with the increase in crystallinity. The inventors of the present invention have conducted research and found that by controlling the rigid amorphous fraction within the above range, even when the orientation anisotropy within the film surface is increased, the embrittlement of the polyethylene terephthalate resin film accompanying the crystallization is more effectively suppressed, and it is easier to suppress the fracture starting from the cut portion in the slitting process or the polyethylene terephthalate resin film being cut and producing fine powder.
[0070] In the above formula (2), the rigid amorphous fraction is indirectly calculated using the values of the flexible amorphous fraction and the mass fraction crystallinity. The flexible amorphous fraction is obtained by the reversible heat capacity difference ΔCp under Tg of the reversible heat capacity curve obtained by temperature modulation DSC measurement using a differential scanning calorimeter (manufactured by TA Instrument, Q100). On the other hand, the mass fraction crystallinity is calculated by the value of the density obtained using a density gradient tube in accordance with JIS K7112. The details are described later in the embodiments. From the viewpoint of controlling the rigid amorphous fraction within the above preferred range, the flexible amorphous fraction is preferably 24.5% by mass or more, more preferably 25% by mass or more, further preferably 25.5% by mass or more, and particularly preferably 26% by mass or more. The upper limit is preferably 36% by mass or less, more preferably 35.5% by mass or less, further preferably 35% by mass or less, and particularly preferably 34.5% by mass or less.
[0071] From the viewpoint of controlling the rigid amorphous fraction within the above preferred range and suppressing embrittlement caused by excessive crystallization, the mass fraction crystallinity is preferably 41 mass % or less, more preferably 40 mass % or less, further preferably 39 mass % or less, and particularly preferably 38 mass % or less. The lower limit is 27 mass % or more, more preferably 28 mass % or more, further preferably 29 mass % or more, and particularly preferably 30 mass % or more.
[0072] The polyethylene terephthalate resin film of the present invention can be produced based on a conventional polyester film production method. For example, the following method can be cited: the polyethylene terephthalate resin is melted, the non-oriented polyethylene terephthalate resin extruded into a sheet is stretched in the longitudinal direction at a temperature above the glass transition temperature by using a roller speed difference, and then stretched in the transverse direction by using a tenter, and heat-treated. Alternatively, a simultaneous biaxial stretching machine can be used to simultaneously or sequentially stretch in the longitudinal and transverse directions in the tenter.
[0073] The film-forming conditions of the polyethylene terephthalate resin film are specifically described. The present inventors have studied day and night and found that by preheating at a sufficiently high temperature to soften the film sufficiently, and then stretching at a temperature appropriately lower than the preheating temperature, the orientation of the amorphous molecular chains during stretching can be promoted, and the mesophase orientation parameter can be effectively increased. The stretching temperature is preferably at least 5°C lower than the preheating temperature.
[0074] The upper limit of the stretching temperature is more preferably a temperature lower than the preheating temperature by 10°C or more, further preferably a temperature lower by 15°C or more, and particularly preferably a temperature lower by 20°C or more. The lower limit of the stretching temperature is more preferably a preheating temperature-60°C or more, further preferably a preheating temperature-55°C or more, and particularly preferably a preheating temperature-50°C or more. By setting the stretching temperature to the above range, the film temperature during stretching is easily controlled, and the mesophase orientation parameter is easily adjusted.
[0075] The specific conditions for longitudinal stretching and transverse stretching are described. The preheating temperature is preferably above 100°C, more preferably above 105°C, further preferably above 108°C, and particularly preferably above 110°C. The preheating temperature is preferably below 150°C, more preferably below 140°C, further preferably below 135°C, and particularly preferably below 130°C. If the preheating temperature is too low, the orientation of the amorphous molecular chains is difficult, and there is a tendency to make it difficult to fully increase the orientation parameters of the intermediate phase. On the other hand, if the preheating temperature is too high, there is a tendency to easily produce uneven thickness during stretching. The preheating time varies depending on the heating method. For example, when heating is performed using hot air from a tentering machine, it is preferably 1 to 120 seconds, more preferably 2 to 60 seconds. The appropriate time can also be set in consideration of the thickness of the film, wind speed, etc.
[0076] In addition, the stretching temperature is preferably above 85°C, more preferably above 88°C, and further preferably above 90°C. The stretching temperature is preferably below 105°C, more preferably below 102°C, and further preferably below 100°C. If the stretching temperature is too high, the tensile stress is insufficient, and in addition to causing thickness unevenness, there is a tendency for it to be difficult to sufficiently increase the intermediate phase orientation parameter. On the other hand, if the stretching temperature is too low, there is a tendency for excessive crystal growth to make it difficult to sufficiently increase the intermediate phase orientation parameter. The inventors have found that by controlling the stretching temperature within the above range, even when the preheating temperature is increased, the thickness unevenness can be suppressed, and the intermediate phase orientation parameter can be effectively increased.
[0077] The above conditions are preferably applied to at least the stretching in the main stretching direction. However, when the main stretching is performed in the longitudinal direction using the speed difference of the rollers, the strain rate is usually sufficiently large and the orientation of the amorphous molecular chains is easy to proceed, so the above conditions may not be applied.
[0078] In the case of manufacturing a film having a slow axis in the width direction of the film (TD direction), the longitudinal stretching ratio is preferably 0.7 times or more, more preferably 0.8 times or more, further preferably 0.9 times or more, and particularly preferably 0.95 times or more. The longitudinal stretching ratio is preferably 1.5 times or less, more preferably 1.3 times or less, further preferably 1.2 times or less, particularly preferably 1.1 times or less, and most preferably 1.05 times or less. Furthermore, longitudinal stretching may not be performed, that is, the longitudinal stretching ratio is 1 times. By setting the above range, the film is difficult to crack in the transverse direction, and it is easy to impart a large refractive index difference and various characteristics of the present invention. The transverse stretching ratio is preferably 4.0 to 7.0 times. In addition, from the viewpoint of suppressing the relaxation of amorphous molecular chains during stretching and increasing the rigid amorphous fraction, it is preferred to increase the transverse stretching ratio. The lower limit of the transverse stretching ratio is more preferably 4.5 times, more preferably 4.7 times, and particularly preferably 5.0 times. On the other hand, if the transverse stretching ratio exceeds 7.0 times, the film is easy to crack in the transverse direction, and there is a tendency for productivity to decrease. Therefore, the upper limit of the transverse stretch ratio is more preferably 6.5 times, further preferably 6.0 times, particularly preferably 5.7 times, and most preferably 5.5 times.
[0079] On the other hand, in the case of manufacturing a film having a slow axis in the longitudinal direction (MD direction) of the film, the transverse stretching ratio is preferably 0.7 times or more, more preferably 1.0 times or more, further preferably 1.3 times or more, further preferably 1.5 times or more, particularly preferably 1.7 times or more, and most preferably 2.0 times or more. The transverse stretching ratio is preferably 3.0 times or less, more preferably 2.7 times or less, and further preferably 2.5 times or less. By setting the above range, the film is difficult to crack in the longitudinal direction, and it is easy to give a large refractive index difference and various characteristics of the present invention. In particular, when the film of the present invention is used as a polarizer protective film to form a polarizing plate bonded to a polarizer having PVA stretched in the length direction, in order to suppress the polarizing plate from becoming easy to crack or break in the length direction, the transverse stretching ratio is preferably greater than 1 times. From the viewpoint of suppressing the relaxation of amorphous molecular chains in stretching and increasing the rigid amorphous fraction, it is preferred to increase the longitudinal stretching ratio. The longitudinal stretching ratio is preferably 4.0 times or more, more preferably 4.5 times or more, further preferably 4.7 times or more, and particularly preferably 5.0 times or more. If the longitudinal stretching ratio is too high, the film is easy to split in the longitudinal direction, and the productivity is reduced, so the longitudinal stretching ratio is preferably 7.0 times, more preferably 6.5 times, and particularly preferably 6.0 times. By setting the longitudinal stretching ratio and the transverse stretching ratio to the above ranges, respectively, the rigid amorphous fraction can be effectively improved, but on the other hand, with the increase of the stretching ratio in the slow axis direction, crystal growth is dominant, and there is a tendency to be difficult to fully increase the mesophase orientation parameter. Therefore, in order to promote the orientation of the amorphous molecular chain in the stretching, the mesophase orientation parameter is controlled within the above range, as described above, preferably after preheating at a sufficiently high temperature, it is stretched at a temperature appropriately lower than that thereof.
[0080] In order to control the retardation within the above range, it is preferred to control the ratio of the longitudinal stretch ratio to the transverse stretch ratio, the stretching temperature, and the thickness of the film. If the difference between the longitudinal and transverse stretch ratios is too small, it tends to be difficult to increase the retardation.
[0081] In order to effectively suppress the embrittlement of the polyethylene terephthalate resin film accompanying crystallization during heat treatment, it is preferred to increase the rigid amorphous fraction. Specifically, it is preferred to suppress the relaxation of the amorphous molecular chain during stretching, and it is preferred to increase the strain rate of the film in the stretching direction of the slow axis. The strain rate is preferably 13% / sec or more, more preferably 15% / sec or more, and particularly preferably 17% / sec or more. When stretching is performed using a tenter stretching machine, the upper limit is preferably 60% / sec from the perspective of film forming properties. In the case of roller stretching, there is no particular upper limit on the strain rate, but it is preferably a speed range that can stably transport the film, for example, the conveying speed of the high-speed side roller is preferably 600m / min or less. Here, the strain rate is a parameter represented by (nominal strain (%) in the stretching direction to the slow axis) / (required time (sec) in the stretching direction to the slow axis), and the nominal strain (%) is obtained by ((deformation (mm)) / (initial length (mm)))×100.
[0082] In the subsequent heat treatment, from the viewpoint of promoting oriented crystallization and increasing the delay amount, it is necessary to perform the treatment at a high temperature sufficient to promote oriented crystallization. On the other hand, the inventors of the present invention have conducted in-depth research and found that by dividing the aforementioned heat treatment into two stages of low-temperature treatment followed by high-temperature treatment, it is possible to suppress excessive growth of crystals and prevent the decrease of the intermediate phase orientation parameter, and it is possible to effectively suppress the increase of cutting resistance and embrittlement of the film. The heat treatment temperature during high-temperature treatment is preferably a temperature at least 5°C higher than the heat treatment temperature during low-temperature treatment.
[0083] As the temperature of the high temperature treatment, as the lower limit, it is more preferably a temperature 10°C or higher than the temperature of the low temperature treatment, further preferably a temperature 15°C or higher, and particularly preferably a temperature 20°C or higher. The upper limit temperature of the high temperature treatment is more preferably the temperature of the low temperature treatment + 80°C or lower, further preferably the temperature of the low temperature treatment + 75°C or lower, particularly preferably the temperature of the low temperature treatment + 70°C or lower, and most preferably the temperature of the low temperature treatment + 65°C or lower.
[0084] Specifically, the heat treatment temperature during high temperature treatment is preferably 150°C or more, more preferably 160°C or more, particularly preferably 170°C or more, and most preferably 180°C or more. On the other hand, from the viewpoint of suppressing excessive growth of crystals and preventing the decrease in the orientation parameter of the intermediate phase, the heat treatment temperature during high temperature treatment is preferably 220°C or less, more preferably 210°C or less, and particularly preferably 200°C or less. In addition, the heat treatment temperature during low temperature treatment is preferably 100°C or more, more preferably 110°C or more, particularly preferably 120°C or more, and most preferably 130°C or more. On the other hand, from the viewpoint of suppressing excessive growth of crystals and preventing the decrease in the orientation parameter of the intermediate phase, the heat treatment temperature during low temperature treatment is preferably 170°C or less, more preferably 160°C or less, and particularly preferably 150°C or less.
[0085] The high temperature treatment time is preferably 1 second or longer, more preferably 3 seconds or longer, further preferably 5 seconds or longer, and particularly preferably 7 seconds or longer. The high temperature treatment time is preferably 60 seconds or shorter, more preferably 40 seconds or shorter, and further preferably 30 seconds or shorter.
[0086] The preferred time range for low temperature treatment is also the same as that for high temperature treatment.
[0087] It should be noted that, for example, in the cooling after high-temperature treatment, by reducing the air volume of the cooling air, it appears that the temperature region of the low-temperature treatment is passed for a certain period of time, but in order to stabilize production, it is preferably passed through an oven in a temperature region such as the temperature of the low-temperature treatment.
[0088] By setting the high-temperature heat treatment and the low-temperature heat treatment in the above-mentioned ranges, it is possible to exert the effect of the heat treatment and to ensure productivity.
[0089] After the low-temperature treatment, the film is cooled to a temperature at which it can be rolled up, and the width end portions are cut as necessary to roll up the film.
[0090] In order to adjust the thermal shrinkage of the film, a relaxation treatment may be performed between the heat treatment and the cooling. The relaxation treatment is performed by shrinking in at least one of the TD direction and the MD direction. The relaxation rate is preferably 0.1 to 5%, more preferably 0.2 to 4%. The relaxation treatment may be performed during the high temperature treatment, during the period from the high temperature treatment to the low temperature treatment, during the low temperature treatment, or during the cooling, and may also be performed across multiple steps.
[0091] The present inventors have discovered that by simultaneously carrying out preheating at a sufficiently high temperature and then stretching at a lower temperature than the preheating temperature, and dividing the heat treatment into two stages of a low-temperature treatment followed by a high-temperature treatment, the intermediate phase orientation parameter can be effectively improved, and the breakage starting from the cut portion in the slitting process, the fine powder caused by the cutting of the polyethylene terephthalate resin film, and the convex edge of the end of the product roll caused by the elongation of the film can be effectively suppressed, thereby completing the present invention.
[0092] The polyethylene terephthalate resin constituting the polyethylene terephthalate resin film preferably has 85 mol% or more of the monomer units as ethylene terephthalate. The ethylene terephthalate unit is preferably 90 mol% or more, more preferably 95 mol% or more. It should be noted that as a copolymer component, a known acid component or a diol component may be included. As the polyethylene terephthalate resin, polyethylene terephthalate as a homopolymer is particularly preferred.
[0093] These resins have excellent transparency, thermal and mechanical properties, and can easily control the retardation by stretching. Polyethylene terephthalate has a large intrinsic birefringence, and can easily obtain a large retardation even if the film thickness is thin, making it the most suitable material.
[0094] In addition, for the purpose of suppressing the deterioration of optical functional pigments such as iodine pigment, the light transmittance of the wavelength 380nm of the polyethylene terephthalate resin film of the present invention can be below 20%. The 380nm light transmittance is more preferably below 15%, further preferably below 10%, and particularly preferably below 5%. If the aforementioned light transmittance is below 20%, the optical functional pigment can be suppressed to deteriorate because of ultraviolet rays. It should be noted that the light transmittance in the present invention is measured on the direction perpendicular to the plane of the film, and can be measured using a spectrophotometer (for example, Hitachi U-3500 type).
[0095] In order to make the light transmittance of the polyethylene terephthalate resin film of the present invention at a wavelength of 380nm less than 20%, it is preferred to appropriately adjust the type, concentration and thickness of the ultraviolet absorber. The ultraviolet absorber used in the present invention is a well-known substance. As ultraviolet absorbers, organic ultraviolet absorbers and inorganic ultraviolet absorbers can be mentioned. From the viewpoint of transparency, organic ultraviolet absorbers are preferred. As organic ultraviolet absorbers, benzotriazole, benzophenone, cyclic imino ester, etc. and their combinations can be mentioned. As long as they are within the above-mentioned absorbance range, there is no particular limitation. However, from the viewpoint of durability, benzotriazole and cyclic imino ester are particularly preferred. When two or more ultraviolet absorbers are used in combination, ultraviolet rays of different wavelengths can be absorbed simultaneously, so the ultraviolet absorption effect can be further improved.
[0096] Examples of the benzophenone-based ultraviolet absorbers, benzotriazole-based ultraviolet absorbers, and acrylonitrile-based ultraviolet absorbers include 2-[2'-hydroxy-5'-(methacryloyloxymethyl)phenyl]-2H-benzotriazole, 2-[2'-hydroxy-5'-(methacryloyloxyethyl)phenyl]-2H-benzotriazole, 2-[2'-hydroxy-5'-(methacryloyloxypropyl)phenyl]-2H-benzotriazole, 2,2'-dihydroxy-4,4'-dimethoxybenzophenone, 2,2',4,4'-tetrahydroxybenzophenone, 2,4-di-tert-butyl-6-(5-chlorobenzotriazol-2-yl)phenol, 2-(2'-hydroxy-3 '-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole, 2-(5-chloro(2H)-benzotriazol-2-yl)-4-methyl-6-(tert-butyl)phenol, 2,2'-methylenebis(4-(1,1,3,3-tetramethylbutyl)-6-(2H-benzotriazol-2-yl)phenol, etc. Examples of the cyclic iminoester-based ultraviolet light absorber include 2,2'-(1,4-phenylene)bis(4H-3,1-benzoxazine-4-one), 2-methyl-3,1-benzoxazine-4-one, 2-butyl-3,1-benzoxazine-4-one, and 2-phenyl-3,1-benzoxazine-4-one. However, the present invention is not particularly limited thereto.
[0097] In addition, in addition to the ultraviolet light absorber, various additives other than the catalyst are also preferably contained within the scope of not hindering the effect of the present invention. As additives, for example, inorganic particles, heat-resistant polymer particles, alkali metal compounds, alkaline earth metal compounds, phosphorus compounds, antistatic agents, light-resistant agents, flame retardants, heat stabilizers, antioxidants, anti-gelling agents, surfactants, etc. can be cited. In addition, in order to give play to high transparency, it is also preferred that the polyethylene terephthalate resin film does not substantially contain particles. "Substantially does not contain particles" means that, for example, in the case of inorganic particles, when the inorganic elements are quantitatively analyzed by fluorescent X-ray analysis, it is less than 50ppm, preferably less than 10ppm, and particularly preferably the content below the detection limit.
[0098] In addition, as a method for blending an ultraviolet absorber into the polyethylene terephthalate resin film in the present invention, a combination of known methods can be used, for example, a masterbatch can be prepared by pre-blending the dried ultraviolet absorber and the polymer raw material using a kneading extruder, and then the masterbatch and the polymer raw material can be mixed during film formation.
[0099] At this time, in order to make the ultraviolet absorber uniformly dispersed and economically matched, the ultraviolet absorber concentration of the masterbatch is preferably a concentration of 5 to 30% by mass. As a condition for making the masterbatch, a mixing extruder is used, and the extrusion temperature is preferably extruded for 1 to 15 minutes at a temperature above the melting point of the polyethylene terephthalate raw material and below 290°C. If it is above 290°C, the reduction amount of the ultraviolet absorber is large, and the viscosity of the masterbatch is reduced. If the extrusion time is less than 1 minute, there is a tendency that the ultraviolet absorber is difficult to mix uniformly. At this time, stabilizers, color tone regulators, and antistatic agents can be added as needed.
[0100] In addition, in the present invention, the film can be made into a multilayer structure of at least 3 layers, and an ultraviolet absorber is added to the middle layer of the film. Specifically, a three-layer film containing an ultraviolet absorber in the middle layer can be made as follows. As an outer layer, pellets of polyethylene terephthalate resin are used alone, and as an middle layer, a masterbatch containing an ultraviolet absorber and pellets of polyethylene terephthalate resin are mixed in a specified ratio, and after drying, they are supplied to a known melt lamination extruder, extruded into a sheet from a slit-shaped die, and cooled and solidified on a casting roll to make an unstretched film. That is, using more than two extruders, a three-layer manifold or a confluence block (for example, a confluence block with a square confluence portion), the film layers constituting the two outer layers and the film layers constituting the middle layer are stacked, and a three-layer sheet is extruded from a nozzle, and the unstretched film is made by cooling with a casting roll. It should be noted that in order to remove foreign matter contained in the raw material polyethylene terephthalate resin that is the cause of optical defects, it is preferred to perform high-precision filtration during melt extrusion. The filter particle size (initial filtration efficiency 95%) of the filter material used for high-precision filtration of the molten resin is preferably 15 μm or less. If the filter particle size of the filter material exceeds 15 μm, the removal of foreign matter above 20 μm is likely to become insufficient.
[0101] Furthermore, the polyethylene terephthalate resin film of the present invention may be subjected to corona treatment, coating treatment, flame treatment or the like in order to improve the adhesiveness of the film surface.
[0102] In the present invention, in order to make the adhesion of the polyethylene terephthalate resin film surface good, it is preferred to have an easy-adhesion layer (adhesion modified coating layer) on at least one side of the film of the present invention. The easy-adhesion layer can appropriately adopt the easy-adhesion layer known in the past, but it is preferred to use at least one of polyester resin, polyurethane resin or polyacrylic resin as the main component. Here, "main component" refers to the component of more than 50% by mass of the solid content constituting the easy-adhesion layer. The coating liquid for forming the easy-adhesion layer is preferably an aqueous coating liquid containing at least one of a water-soluble or water-dispersible copolyester resin, an acrylic resin and a polyurethane resin. Examples of these coating liquids include water-soluble or water-dispersible copolyester resin solutions, acrylic resin solutions, and polyurethane resin solutions disclosed in Japanese Patent Nos. 3567927, 3589232, 3589233, 3900191, and 4150982.
[0103] The easy-adhesive layer can be obtained by, for example, applying the coating solution to one or both sides of an unstretched film or a uniaxially stretched film in the longitudinal direction, drying at 100 to 150°C, and further stretching in the transverse direction. The final coating amount of the easy-adhesive layer is preferably managed to be 0.05 to 0.20 g / m 2 If the coating amount is less than 0.05g / m 2 On the other hand, if the coating amount exceeds 0.20 g / m 2 , sometimes the blocking resistance is reduced. In addition, from the viewpoint of obtaining a good coating appearance, the thickness of the final easy-adhesive layer obtained after stretching is preferably 1 μm or less, more preferably 0.5 μm or less, and further preferably 0.2 μm or less. In the case where easy-adhesive layers are provided on both sides of the polyethylene terephthalate resin film, the coating amounts of the easy-adhesive layers on both sides may be the same or different, and may be independently set within the above range.
[0104] In order to impart slipperiness to the easy-adhesive layer, it is preferred to add particles. It is preferred to use particles with an average particle size of less than 2 μm. If the average particle size of the particles exceeds 2 μm, the particles are easy to fall off from the coating layer. As particles contained in the easy-adhesive layer, for example, inorganic particles such as titanium oxide, barium sulfate, calcium carbonate, calcium sulfate, silicon dioxide, aluminum oxide, talc, kaolin, clay, calcium phosphate, mica, hectorite, zirconium oxide, tungsten oxide, lithium fluoride, calcium fluoride, styrene-based, acrylic acid-based, melamine-based, benzoguanamine-based, silicone-based, etc. can be cited. Organic polymer particles, etc., can be added to the easy-adhesive layer alone, or two or more can be added in combination.
[0105] In addition, as a method for applying the coating liquid, a known method can be used. For example, reverse roll coating, gravure coating, kiss coating, roller brushing, spray coating, air knife coating, wire rod coating, tubular scraping, etc. can be mentioned, and these methods can be carried out alone or in combination.
[0106] In addition, the average particle size of the above particles was measured by the following method.
[0107] The particles are photographed using a scanning electron microscope (SEM), and the maximum diameters (the distance between the two farthest points) of 300 to 500 particles are measured at a magnification such that the size of the smallest particle is 2 to 5 mm. The average value is taken as the average particle size.
[0108] It is also a preferred embodiment that a functional layer such as a hard coat layer, an antireflection layer, a low reflection layer, an antiglare layer, a light diffusion layer, a lens layer, or a prism layer is laminated on at least one side of the polyethylene terephthalate resin film of the present invention via an easy adhesion layer.
[0109] The thickness of the polyethylene terephthalate resin film of the present invention is arbitrary, preferably in the range of 25 to 300 μm. Even a film with a thickness of less than 25 μm can, in principle, obtain a retardation of 3000 nm or more. However, in this case, the anisotropy of the mechanical properties of the film becomes significant, and there is a tendency to easily generate cracks, ruptures, etc.
[0110] The upper limit of the polyethylene terephthalate resin film of the present invention is preferably 200 μm, 150 μm, 120 μm, 100 μm, 90 μm, 80 μm, 75 μm, and 70 μm, and the lower limit is 30 μm, 35 μm, 40 μm, 45 μm, and 50 μm.
[0111] The polyethylene terephthalate resin film of the present invention can be used for various applications, and the optimal thickness range can be selected from the above range according to the application.
[0112] For example, when the polyethylene terephthalate resin film of the present invention is used as a polarizer protective film, the upper limit of the thickness can be selected to be below 120 μm from the viewpoint of practicality, and the lower limit is as described above. From the viewpoint of thinner thickness in recent years, it is more preferably below 65 μm, more preferably below 60 μm, and particularly preferably below 55 μm.
[0113] When the polyethylene terephthalate resin film of the present invention is used as a substrate of a transparent conductive film, the preferred range is the same as that listed for the polarizer protective film when used as an anti-scattering film.
[0114] When the polyethylene terephthalate resin film of the present invention is used as a surface protection film such as a cover plate of an image display device, the lower limit of the thickness can be selected from the above lower limit value to a value of 40 μm or more, and the upper limit of the thickness can be selected from the above upper limit value to a value of 150 μm or more.
[0115] In recent years, the demand for further thinning of polarizer protective films has become stronger, and the processing adaptability of polarizer protective films has tended to be reduced. Even in such a case, according to the present invention, it is possible to effectively suppress the increase in cutting resistance in the fast axis direction, the embrittlement of the polyethylene terephthalate resin film, and the fracture starting from the cut portion during the slitting process, the generation of fine powder caused by the cutting of the polyethylene terephthalate resin film, and the generation of convex edges at the ends of the product rolls caused by the elongation of the film.
[0116] In order to suppress the variation of the delay amount, the thickness unevenness of the film is preferably small. The stretching temperature and the stretching ratio have a great influence on the uneven thickness of the film, so from the perspective of uneven thickness, it is preferred to optimize the film-making conditions. In particular, if the longitudinal stretching ratio is reduced in order to increase the delay amount, the longitudinal thickness unevenness sometimes deteriorates. Since there is a region where the longitudinal thickness unevenness becomes very poor within a specific range with a stretching ratio, it is preferred to set the film-making conditions in a manner deviating from this range.
[0117] The thickness unevenness of the film of the present invention is preferably 5.0% or less, more preferably 4.5% or less, further preferably 4.0% or less, and particularly preferably 3.0% or less.
[0118] The polyethylene terephthalate resin film of the present invention preferably has an Nz coefficient represented by |ny-nz| / |ny-nx| of 1.7 or less. The Nz coefficient can be obtained as follows. A molecular orientation meter (manufactured by Oji Scientific Instruments, MOA-6004 molecular orientation meter) is used to obtain the orientation axis direction of the film, and an Abbe refractometer (manufactured by ATAGO CO., LTD., NAR-4T, measuring wavelength 589 nm) is used to obtain the biaxial refractive index (ny, nx, where ny>nx) in the orientation axis direction and the direction orthogonal thereto, and the refractive index (nz) in the thickness direction. Substituting the thus obtained nx, ny, and nz into the formula represented by |ny-nz| / |ny-nx|, the Nz coefficient can be obtained. The Nz coefficient is more preferably less than 1.65, and further preferably less than 1.63. The lower limit of the Nz coefficient is preferably 1.2. In order to maintain the mechanical strength of the film, the lower limit of the Nz coefficient is preferably 1.3 or more, more preferably 1.4 or more, and further preferably 1.45 or more.
[0119] The ratio (Re / Rth) of the retardation (Re) of the polyethylene terephthalate resin film to the retardation in the thickness direction (Rth) is preferably 0.2 or more, more preferably 0.5 or more, and further preferably 0.6 or more. The larger the above ratio (Re / Rth), the more preferred. The upper limit is preferably 2.0 or less, more preferably 1.8 or less. It should be noted that the retardation in the thickness direction is a parameter representing the average of the retardation obtained by multiplying the two birefringences ΔNxz (=|nx-nz|) and ΔNyz (=|ny-nz|) respectively by the film thickness d when observed from the cross section in the thickness direction of the film. nx, ny, nz and film thickness d (nm) can be obtained, and the average values of (ΔNxz×d) and (ΔNyzd×d) are calculated to obtain the retardation in the thickness direction (Rth). It should be noted that nx, ny, and nz are obtained by an Abbe refractometer (manufactured by ATAGO CO., LTD., NAR-4T, measuring wavelength 589nm).
[0120] The surface roughness (SRa) (JIS B0601: 1994) of the polyethylene terephthalate resin film is preferably 0.05 μm or less, more preferably 0.01 μm or less, and further preferably 0.005 μm or less on at least one side and both sides. By setting the SRa to 0.05 μm or less, a highly transparent film can be produced. In addition, in order to ensure the slipperiness of the film, the SRa is preferably 0.0001 μm or more, and further preferably 0.0005 μm or more.
[0121] The ten-point average surface roughness (SRz) (JIS B0601: 1994) of the polyethylene terephthalate resin film is preferably 1.0 μm or less, more preferably 0.70 μm or less, further preferably 0.50 μm or less, particularly preferably 0.30 μm or less, and most preferably 0.2 μm or less on at least one side and further preferably 0.005 μm or less. The SRz is preferably 0.001 μm or more, further preferably 0.005 μm or more.
[0122] The phenomenon of increased surface roughness is mostly caused by coarse particles such as particle agglomerates and catalyst residues. If the surface roughness is below the above upper limit, it can prevent coarse particles from falling off and damaging the surface of the film during the manufacturing and processing steps of the film and after being assembled as a liquid crystal display device, and it can also suppress the formation of bright spots or dark spots that reduce the image quality. In addition, it can also suppress the reduction of image clarity and contrast.
[0123] Coarse particles in the film are preferably removed by a method such as removing them with a filter during the production of the resin or installing a filter in a film production line.
[0124] When the surface is an adhesive layer or other coating layer, it is preferable to filter the coating solution after preparation or to install a filter in the line conveying the coating solution to the coating die.
[0125] The number of foreign matters with a major diameter of 100 μm or more in the polyethylene terephthalate resin film is preferably 2 or less. The foreign matters with a major diameter of 100 μm or more in the polyethylene terephthalate resin film are as follows: the foreign matters are placed on the polyethylene terephthalate resin film side of the polarizing plate cut into a size to be assembled in the image display device in a manner to form an orthogonal Nicol, and the major diameter of the foreign matters observed as bright spots is 100 μm or more. As foreign matters in the film, for example, agglomerates of lubricant particles can be cited. It is not only preferred to remove agglomerates using a filter with a small pore size during film formation, but it is also preferred to use lubricant particles only in the surface layer of the film as a multilayer structure. In addition, it is also preferred to use lubricant particles in the film instead of using lubricant particles in the easy-to-adhesive coating on the surface.
[0126] Furthermore, degraded resins may also become foreign matter in the film. If it is a hard foreign matter in the molten resin, it can be removed by the above-mentioned filter, but gel-like foreign matter that is thermally degraded by the molten resin can be deformed to a certain extent at the temperature of the molten resin, so even if it is larger than the pore size of the filter, it may sometimes pass through the filter. In the case of large thermally degraded products, it may be cut off by the filter and the number of foreign matter may increase. In addition, thermally degraded resins produced in the pipeline after the filter are directly included in the film. These foreign matters not only cannot follow the stretching orientation of the surrounding resins during the stretching process, but also disturb the stretching orientation of the surrounding resins, and appear as bright spots when measured by the orthogonal Nicol method. In addition, even small hard foreign matters that pass through the filter will form gaps (pores) between the resin and the filter during stretching, and sometimes become foreign matters in the film. In addition, the pore size of the filter does not mean that foreign matters larger than the pore size can pass through. Even foreign matters larger than the pore size can pass through at a certain ratio.
[0127] The number of foreign matter having a major diameter of 100 μm or more in the polyethylene terephthalate-based resin film is more preferably 1 or less, and preferably 0, that is, no foreign matter.
[0128] The number of foreign particles having a major diameter of 50 μm or more in the polyethylene terephthalate-based resin film is preferably 5 or less, more preferably 3 or less, further preferably 1 or less, and particularly preferably 0.
[0129] Furthermore, the number of foreign particles having a major diameter of 20 μm or more in the polyethylene terephthalate resin film is preferably 10 or less, more preferably 5 or less, further preferably 3 or less, particularly preferably 1 or less, and most preferably 0.
[0130] If such foreign matter exists in the polyethylene terephthalate resin film, not only will the colored foreign matter be observed when the image is observed nearby, but even if it is a substantially colorless transparent foreign matter, due to the difference in refractive index between the normal part of the surrounding area, it may become a different color in a tiny part, or the uniformity of the color tone may be disturbed. In addition, in the case of the polarizing plate on the light source side, it may become a dark spot.
[0131] In order to reduce the above-mentioned foreign matter in the film, it is preferred to minimize the part of the path through which the molten resin passes where the resin is retained. Specifically, in the extruder, it is preferred to minimize the step difference between the screw elements, the step difference between the blocks of the barrel, and the step difference between the connecting parts of the piping. In addition, it is preferred to design the piping, the housing of the filter, the filter element, the flow path of the joint, etc. to reduce the retention of the resin, or reduce the roughness of their inner walls.
[0132] In addition, there is a tendency that foreign matter increases when the production of the film starts or the resin extrusion amount is increased. In these cases, it is also preferred to temporarily increase the resin extrusion amount and then reduce it to a specified amount.
[0133] Furthermore, it is preferable to take measures such as inspecting the film for defects after film formation so as not to use the film with a large amount of foreign matter for the production of polarizing plates, marking defective parts and not using the polarizing plates of those parts.
[0134] The haze of the polyethylene terephthalate resin film is preferably 5% or less, more preferably 3% or less, further preferably 2% or less, and particularly preferably 1.5% or less. The lower limit of the haze is preferably 0.01% or more, further preferably 0.1% or more.
[0135] It should be noted that SRa and SRz are respectively the SRa and SRz of the surface of the polyethylene terephthalate resin film of the blank before coating with a functional layer such as a low reflection layer described later, but when the easy adhesion layer is provided in-line, the value is the value of the easy adhesion layer. The same applies to haze.
[0136] The haze can be measured in accordance with JIS-K7105 using a turbidity meter (NHD2000, manufactured by NIPPON DENSHOKU INDUSTRIES Co., Ltd.).
[0137] The intrinsic viscosity (IV) of the resin constituting the film is preferably 0.45 to 1.5 dL / g.
[0138] In the case of PET, IV is preferably 0.5 to 1.5 dL / g. The lower limit of IV is more preferably 0.53 dL / g, and further preferably 0.55 L / g. The upper limit of IV is more preferably 1.2 dL / g, further preferably 1 dL / g, and particularly preferably 0.8 dL / g.
[0139] In the case of PEN, the lower limit of IV is preferably 0.45 dL / g, more preferably 0.48 dL / g, further preferably 0.5 dL / g, and particularly preferably 0.53 dL / g. The upper limit of IV is more preferably 1 dL / g, more preferably 0.8 dL / g, further preferably 0.75 dL / g, and particularly preferably 0.7 dL / g.
[0140] By setting the above range, a thin film having excellent mechanical strength such as impact resistance can be obtained, and it can be efficiently manufactured without applying a large load to the equipment. In addition, IV is measured by dissolving 0.2 g of a sample in 50 ml of a mixed solvent of phenol / 1,1,2,2-tetrachloroethane (60 / 40 (weight ratio)) at 30°C using an Ostwald viscometer.
[0141] In the polarizer protective film, the amount of antimony atoms in the residue insoluble in the mixed solvent of p-chlorophenol and tetrachloroethane is preferably 50 mg or less, more preferably 30 mg or less, further preferably 20 mg or less, particularly preferably 10 mg or less, and most preferably 5 mg or less, relative to 1 kg of the resin constituting the film. The less the amount of antimony atoms in the residue, the better. As a lower limit, it is preferably 0.1 mg, more preferably more than 0.5 mg, and further preferably more than 1 mg. The polarizer protective film is preferably formed of a resin, particularly a polyester resin, polymerized using an antimony compound as a catalyst.
[0142] Examples of the antimony compound used as the catalyst include antimony trioxide, antimony pentoxide, antimony acetate, antimony glycolate, etc., and antimony trioxide (Sb2O3) is preferred.
[0143] Furthermore, as the catalyst, in addition to the antimony compound, a titanium compound catalyst such as tetrabutoxytitanate, basic aluminum acetate, and an aluminum-based catalyst containing a phosphate ester of a hindered phenol (eg, Irganox 1222) may be used in combination.
[0144] Furthermore, it is also preferred to add a polymerization stabilizer, an auxiliary agent, or a melt resistivity adjuster. Representative substances include phosphorus compounds such as trimethyl phosphate and phosphoric acid, magnesium compounds such as magnesium acetate, and calcium compounds such as calcium acetate.
[0145] In order to make the amount of antimony atoms in the residue insoluble in the mixed solvent of the film below the above amount, it is preferred to make the amount of antimony atoms in the residue insoluble in the mixed solvent of the resin used in producing the film below the above amount.
[0146] Examples of methods for making the amount of antimony atoms in the residue insoluble in the mixed solvent of the polyester resin to be the following include the following methods, and these methods may be used alone or in combination of two or more.
[0147] The amount of antimony added is set to an antimony atomic weight of preferably 300 ppm or less, more preferably 250 ppm or less, further preferably 220 ppm or less, and particularly preferably 200 ppm or less, relative to the polyester resin after polymerization. It should be noted that the lower limit of the antimony content is preferably 30 ppm, further preferably 50 ppm or 80 ppm.
[0148] The antimony compound is added in the form of a solution or slurry in ethylene glycol. In this case, the concentration of the antimony compound is preferably 10% by mass or less, more preferably 7% by mass or less, and particularly preferably 5% by mass or less.
[0149] The maximum temperature of the polymerization of the polyester resin is preferably 290° C. or lower, more preferably 285° C. or lower.
[0150] The degree of reduced pressure is increased so that the time to reach the maximum temperature of the polymerization of the polyester resin is within 45 minutes, and further within 30 minutes. In the case of continuous polymerization, the average residence time is used.
[0151] When a phosphorus compound, a magnesium compound or a calcium compound is added, the amount added is preferably 15 to 120 ppm, more preferably 20 to 100 ppm, and still more preferably 25 to 80 ppm in terms of phosphorus atomic weight relative to the polyester resin after polymerization, and the amount of magnesium atomic weight or calcium atomic weight is preferably 30 to 120 ppm, and still more preferably 40 to 100 ppm. It is further preferred to add the phosphorus compound after adding the magnesium compound or the calcium compound, and in this case, add it in multiple stages.
[0152] 2.Polarizing plate
[0153] The polyethylene terephthalate resin film of the present invention can be used as a polarizer protective film. The polarizing plate of the present invention has a structure in which a polarizer protective film formed of the polyethylene terephthalate resin film of the present invention is laminated on at least one surface of the polarizer. The polarizer can use a material dyed with iodine on polyvinyl alcohol (PVA) or the like.
[0154] The surface of the polarizer on the opposite side of the side laminated with the polyethylene terephthalate resin film (referred to as the other side) is preferably a film without birefringence represented by a TAC film, an acrylic film, or a norbornene film. In addition, it is also preferred that a polarizer protective film, an optical compensation film, etc. are not laminated on the other side. In addition, a coating layer such as a hard coating layer may also be laminated on the other side. In the polarizing plate used in the present invention, various hard coating layers are also preferably applied on the surface for the purpose of preventing reflection, suppressing glare, suppressing scratches, etc.
[0155] 3. Image display device
[0156] As described later, the polarizing plate of the present invention can be used as a component of an image display device such as a liquid crystal display device and an organic EL display device.
[0157] 4. Liquid crystal display device
[0158] Generally, a liquid crystal panel is composed of a rear module, a liquid crystal unit, and a front module in the order from the side opposite to the backlight source toward the side where the image is displayed (visible side). The rear module and the front module are generally composed of a transparent substrate, a transparent conductive film formed on the surface of the liquid crystal unit side thereof, and a polarizing plate arranged on the opposite side thereof. Here, the polarizing plate is arranged on the side opposite to the backlight source in the rear module, and on the side where the image is displayed (visible side) in the front module.
[0159] The liquid crystal display device of the present invention comprises at least a backlight source, two polarizing plates, and a liquid crystal unit disposed between the two polarizing plates as components. In addition, other components other than these may be appropriately provided, such as a color filter, a lens film, a diffuser, an anti-reflection film, etc. Of the two polarizing plates, at least one polarizing plate is preferably the polarizing plate of the present invention.
[0160] The structure of the backlight source may be an edge light type using a light guide plate, a reflector, etc. as components, or a direct light type.
[0161] As the backlight source mounted in the liquid crystal display device of the present invention, there is no particular limitation, and a white light source having a peak of the emission spectrum in each wavelength region of 400 nm to less than 495 nm, 495 nm to less than 600 nm, and 600 nm to 780 nm can be preferably used. As such a light source, for example, a white light source using quantum dot technology, a white LED light source using a phosphor having emission peaks in the R (red) and G (green) regions of excitation light and a phosphor-based white LED light source using a blue LED, a three-wavelength white LED light source, a white LED light source combined with a red laser, a blue light emitting diode and a phosphor having at least K2SiF6:Mn 4+ White light-emitting diodes using fluoride phosphor (also called "KSF"), etc.
[0162] In addition, it is also preferable to use a phosphor-type white LED that combines a blue light or ultraviolet light-emitting diode using a compound semiconductor and a phosphor (for example, a yttrium-aluminum-garnet-based yellow phosphor, a terbium-aluminum-garnet-based yellow phosphor, etc.).
[0163] The configuration of the polarizer protective film composed of the polyethylene terephthalate resin film of the present invention in the liquid crystal display device is not particularly limited. In the case of a liquid crystal display device configured with a polarizer configured on the incident light side (light source side), a liquid crystal unit, and a polarizer configured on the exit light side (visible side), the polarizer protective film on the incident light side of the polarizer configured on the incident light side and / or the polarizer protective film on the exit light side of the polarizer configured on the exit light side is preferably the polarizer protective film formed of the polyethylene terephthalate resin film of the present invention. A particularly preferred method is to set the polarizer protective film on the exit light side of the polarizer configured on the exit light side to the polyethylene terephthalate resin film of the present invention. When the polarizer protective film containing the polyethylene terephthalate resin film is configured at a position other than the above, the polarization characteristics of the liquid crystal unit may sometimes change. Since it is not preferable to use the polarizer protective film including the polyethylene terephthalate-based resin film of the present invention at a location where polarization characteristics are required, it is preferably used as a protective film for a polarizing plate at such a specific location.
[0164] The screen size of the liquid crystal display device of the present invention is not particularly limited, but is preferably 32-inch (diagonal length: 32 inches) or larger, more preferably 42-inch or larger, and particularly preferably 50-inch or larger.
[0165] 5. Organic EL display device
[0166] It is preferred to configure a circular polarizer on the visible side of the organic EL display device. External light is reflected by the metal electrode of the organic EL unit and emitted to the visible side. When visually recognized from the outside, the display surface of the organic EL display device sometimes looks like a mirror. In order to shield such mirror reflection of external light, it is preferred to configure a circular polarizer on the visible side of the organic EL unit. Among the above-mentioned polarizing plates of the present invention, for example, a polarizing plate stacked with a 1 / 4 wavelength plate (1 / 4 wavelength layer) can be used as a circular polarizer for an organic EL display device.
[0167] 6. Transparent conductive film and touch panel
[0168] The touch panel usually has one or more transparent conductive films. The transparent conductive film has a structure in which a transparent conductive layer is stacked on a substrate film. As the substrate film, the polyethylene terephthalate resin film of the present invention can be used. There is no particular limitation on the type and method of the touch panel, and examples thereof include a resistive film touch panel and an electrostatic capacitance touch panel.
[0169] The transparent conductive layer can be directly laminated on the substrate film, or can be laminated via an easy adhesion layer and / or various other layers. As other layers, for example, hard coating, refractive index matching (IM) layer and low refractive index layer etc. can be enumerated. The IM layer is for example a laminated structure of a high refractive index layer / low refractive index layer (the transparent conductive film side is a low refractive index layer) itself, and by using it, it is difficult to see the ITO pattern when observing the liquid crystal display screen.
[0170] The transparent conductive layer on the substrate film can be formed by a conductive metal oxide. The conductive metal oxide constituting the transparent conductive layer is not particularly limited, and a conductive metal oxide of at least one metal selected from the group consisting of indium, tin, zinc, gallium, antimony, titanium, silicon, zirconium, magnesium, aluminum, gold, silver, copper, palladium, and tungsten can be used. The metal oxide can further contain metal atoms shown in the above group as needed. Preferred transparent conductive layers are, for example, tin-doped indium oxide (ITO) layers and antimony-doped tin oxide (ATO) layers, preferably ITO layers. In addition, the transparent conductive layer can also be Ag nanowires, Ag ink, self-assembled conductive films of Ag ink, mesh electrodes, CNT inks, and conductive polymers.
[0171] The thickness of the transparent conductive layer is not particularly limited. The transparent conductive layer can be formed according to a known process, for example, vacuum evaporation, sputtering, and ion plating.
[0172] The transparent conductive film of the present invention may be a film patterned by removing a portion of the surface of the transparent conductive layer. The transparent conductive film with a patterned transparent conductive layer has a pattern forming portion in which the transparent conductive layer is formed on the substrate film, and a pattern opening portion in which the transparent conductive layer is not formed on the substrate film. The shape of the pattern forming portion may be, for example, a square shape in addition to a stripe shape.
[0173] 7. Anti-scattering film, surface protection film
[0174] The polyethylene terephthalate resin film of the present invention can be used as an anti-scattering film or a surface protection film to be laminated on the viewing side of an image display panel.
[0175] Example
[0176] Hereinafter, the present invention will be described in more detail by enumerating examples, but the present invention is not limited to the following examples, and can be implemented by applying appropriate changes within the scope of the gist of the present invention, which are all included in the technical scope of the present invention. It should be noted that the evaluation methods of the physical properties in the following examples are as follows.
[0177] (1) Delay (Re)
[0178] The retardation is a parameter defined by the product (ΔNxy×d) of the orthogonal biaxial refractive index anisotropy (ΔNxy=|nx-ny|) on the film and the film thickness d (nm), and is a measure of optical isotropy and anisotropy. The biaxial refractive index anisotropy (ΔNxy) is determined by the following method. A molecular orientation meter (MOA-6004 molecular orientation meter manufactured by Oji Scientific Instruments) is used to determine the slow axis direction of the film, and a 4 cm×2 cm rectangle is cut out in a manner that the slow axis direction is parallel to the long side of the sample for measurement, as a sample for measurement. For this sample, the orthogonal biaxial refractive index (refractive index in the slow axis direction: ny, refractive index in the direction orthogonal to the slow axis direction: nx) and the refractive index in the thickness direction (nz) were obtained by using an Abbe refractometer (manufactured by ATAGO CO., LTD., NAR-4T, measuring wavelength 589 nm), and the absolute value of the biaxial refractive index difference (|nx-ny|) was taken as the anisotropy of the refractive index (ΔNxy). The thickness d (nm) of the film was measured using an electric micrometer (manufactured by Feinpruf GmbH, Millitron 1245D), and the unit was converted into nm. The retardation (Re) was obtained by the product (ΔNxy×d) of the anisotropy of the refractive index (ΔNxy) and the thickness d (nm) of the film.
[0179] (2) Interphase orientation parameters
[0180] The mesophase orientation parameter of the polyethylene terephthalate resin film is represented by the above formula (1), and the slow axis direction 1457 cm-1 was obtained by Fourier transform infrared spectroscopy (ATR-FTIR) based on the total reflection measurement method using a Fourier transform infrared spectrophotometer (FTS 60A / 896 manufactured by Varian). -1 The absorbance A 1457-slow , 795cm in the slow axis direction -1 The absorbance A 795-slow , 1457cm in the fast axis direction -1 The absorbance A 1457-fast , 795cm in the fast axis direction -1 The absorbance A 795-fast The value of is calculated. In the ATR-FTIR measurement, the polarizer is inserted into the optical system, and the ATR prism uses a diamond crystal, so that the incident angle is 45 degrees. At this time, the slow axis of the film is arranged in parallel with the transmission axis of the polarizer inserted into the optical system, and the wave number ν (cm -1 ) infrared absorption spectrum A slow(ν). In addition, the fast axis of the film was arranged in parallel with the transmission axis of the polarizer inserted into the optical system, and the wave numbers ν (cm -1 ) infrared absorption spectrum A fast (ν). Set the cumulative number to 64 for both sample and background, and the wave number resolution to 2 cm -1 , set the measurement wavenumber range to 650-4000cm -1 The infrared absorption spectrum obtained by ATR-FTIR measurement has a different penetration depth into the sample depending on the wave number, and the baseline is bent. Therefore, the infrared absorption spectrum obtained is obtained by measuring the wave number v (cm -1 ) multiplied by the maximum wave number ν within the measurement range MAX (cm -1 ) and each wave number ν(cm -1 ) MAX In each infrared absorption spectrum after baseline correction, 1456.253 cm -1 The absorbance at A 1457-slow or A 1457-fast 、792.7415cm -1 The absorbance at A 795-slow or A 795-fast Here, absorbance refers to the absolute value of the absorption intensity at the corresponding wave number in the infrared absorption spectrum after baseline correction. It should be noted that, during the above measurement, the slow axis direction of the film was obtained using a molecular orientation meter (MOA-6004 molecular orientation meter manufactured by Oji Scientific Instruments). In addition, the direction orthogonal to the slow axis direction in the film plane is set as the fast axis direction.
[0181] (3) Elastic modulus in the slow axis direction
[0182] The elastic modulus in the slow axis direction is evaluated by a tensile test according to Item 10.3.2 of JIS K7161. The test piece is cut into a rectangular shape of 180 mm × 10 mm with the slow axis direction obtained when measuring the delay (Re) as the long side. Draw a 10 mm long marking line parallel to the short side at a position 40 mm inside the two short sides of the test piece, measure the thickness (mm) of the test piece at 5 points in the 100 mm section sandwiched by the marking line, and calculate the average value. The product of the product and the width of the test piece 10 mm is taken as the cross-sectional area (mm) of the test piece. 2). It should be noted that the thickness of the film was measured using an electric micrometer (Millitron 1245D, manufactured by Feinpruf GmbH). The tensile test was performed by holding the area from the marked line to the short side with a chuck in such a way that the long side direction of the test piece became the tensile direction. The tensile test was performed using a precision universal testing machine (Autograph AGX-V, manufactured by Shimadzu Corporation), with the distance between the chucks set to 100 mm and the tensile speed set to 100 mm / min. The load (N) was divided by the initial cross-sectional area (mm 2 ), converted into nominal stress (MPa). In addition, the stroke amount (mm) of the distance between the chucks when each measured value of the load is obtained is divided by the initial distance between the chucks of 100 mm, thereby converting it into nominal strain. The slope of the nominal stress-nominal strain curve between the two points of nominal strain 0.0005 and 0.0025 is calculated to obtain the elastic modulus (MPa) in the slow axis direction. The chuck uses a pneumatic chuck (manufactured by A&D Company, Limited, with a face J-FFA3W-1KN installed on a parallel tightening air pliers J-JFA1-1KN-09), and the air pressure is 0.5 MPa. In addition, the measurement is performed without applying a preliminary force for the purpose of eliminating slack of the test piece.
[0183] (4) Ratio of elastic modulus in the slow axis direction to that in the fast axis direction
[0184] The elastic modulus in the fast axis direction (MPa) was obtained by the same method as the elastic modulus in the slow axis direction. TD and the elastic modulus E in the fast axis direction MD , find the ratio of the elastic modulus in the slow axis direction to the elastic modulus in the fast axis direction E TD / E MD .
[0185] (5) Fracture strength in the slow axis direction
[0186] The breaking strength in the slow axis direction was evaluated by a tensile test according to Item 7.2 of JIS C2318. In the nominal stress-nominal strain curve obtained by measuring the elastic modulus in the slow axis direction, the load at break (N) was divided by the cross-sectional area (mm 2 ), thereby obtaining the breaking strength (MPa) in the slow axis direction.
[0187] (6) Plane orientation coefficient (ΔP)
[0188] Using the value of the refractive index obtained when measuring the retardation (Re), a value obtained by (nx+ny) / 2-nz was defined as the plane orientation coefficient (ΔP).
[0189] (7) Rigid amorphous fraction
[0190] The rigid amorphous fraction is expressed by the above formula (2) and is indirectly calculated from the flexible amorphous fraction and the mass fraction crystallinity value.
[0191] The flexible amorphous fraction is a parameter defined by ((ΔCp of sample) / (ΔCp of completely amorphous))×100 (mass %) based on the reversible heat capacity difference ΔCp (J / (g·K)) at Tg of the reversible heat capacity curve obtained by temperature modulation DSC measurement using a differential scanning calorimeter (manufactured by TA Instrument, Q100). In the case of polyethylene terephthalate, the completely amorphous ΔCp=0.4052 (J / (g·K)). The sample was weighed in an aluminum pan at 2.0±0.2 mg and measured in the MDSC (registered trademark) heating mode with an average heating rate of 5.0°C / min and a modulation period of 60 sec. The measurement data was collected at a sampling frequency of 5 Hz. In addition, indium was used for temperature and heat calibration, and sapphire was used for specific heat calibration.
[0192] The following is a method for calculating Tg and ΔCp. First, plot the first-order derivative F'(T) of the reversible heat capacity curve F(T) at temperature T, take the moving average of every 2401 points for smoothing, and read the value of the temperature at the peak to find Tg. Next, find the straight line G(T) passing through the two points A (Tg-15, F(Tg-15)) and B (Tg+15, F(Tg+15)). Next, within the range of Tg-15≤T≤Tg+15, the temperature at which F(T)-G(T) becomes minimum is set to T1, and the temperature at which it becomes maximum is set to T2. Here, T1 is equivalent to the starting temperature of the glass transition, and T2 is equivalent to the ending temperature of the glass transition, so the value of ΔCp is obtained by ΔCp=F(T2)-F(T1).
[0193] The mass fraction crystallinity χ is the value of density d (g / cm2) obtained using a density gradient tube of a water / calcium nitrate system according to JIS K7112. 3 ), calculated by the following formula.
[0194] χ=(dc / d)×((d-da) / (d-dc))×100(mass%)
[0195] Where, dc: the density of completely crystalline, da: the density of completely amorphous
[0196] In the case of polyethylene terephthalate, dc = 1.498 (g / cm 3 ), da=1.335(g / cm 3 ).
[0197] (8) Operational stability during slitting
[0198] After the polyethylene terephthalate resin film produced by the method described below is wound on a large roll, the operation stability is evaluated by the number of breaks when slitting a range of width: 1000 mm with the center of the large roll as the center. It should be noted that the cutting blade used for slitting is used in the cutting of the previous film equivalent to the comparative example, and the cutting blade removed after exceeding the prescribed usage is reassembled, and the travel speed is 90% of the designed maximum speed of the slitting machine.
[0199] ○: The number of breakages per day was 0.
[0200] △: The number of breakages per day was 1.
[0201] ×: The number of breakages per day is 2 or more.
[0202] (9) The product is rolled up after slitting
[0203] After the polyethylene terephthalate resin film produced by the method described below is wound on a large roll, it is unwound by a slitting machine at a unwinding speed of 185 m / min, while a range of 1000 mm in width is cut out with the center of the large roll as the center, and the winding tension is set to 150 N / m and the winding contact pressure is set to 130 N / m. The end is not knurled, and the roll is wound in the form of a product roll with a roll length of 2000 m, and the convex amount is evaluated. At both ends of the product roll, the height of the end portion when the position 100 mm inside the end is taken as the reference (0 mm) is measured as the convex amount, and the average value of the convex amount at both ends is calculated. It should be noted that the winding tension is the tension when the film is wound into a cylindrical core, and the winding contact pressure is the winding contact pressure of the contact roll at this time while pressing the contact roll during winding.
[0204] ◎: The convex edge is within 1.0mm
[0205] ○: The convex edge is within 2.0 mm
[0206] ×: The convex edge is greater than 2.0 mm
[0207] (10) Observation of rainbow spots
[0208] The polyethylene terephthalate resin film produced by the method described later is pasted on one side of the polarizer formed by PVA and iodine in a manner that the absorption axis of the polarizer is perpendicular to the orientation axis of the film, and a commercially available TAC film is pasted on the opposite side to form a polarizer. The obtained polarizer is used to replace the polarizer on the light emitting side of the commercially available liquid crystal display device (Sharp Corporation, LC32DZ3). It should be noted that the polarizer is replaced in a manner that the absorption axis of the polarizer is consistent with the absorption axis direction of the polarizer originally attached to the liquid crystal display device, and the polyethylene terephthalate resin film becomes the visible side. The above-mentioned liquid crystal display device has a white LED formed by a light-emitting element that combines a blue light emitting diode and a yttrium aluminum garnet yellow phosphor in the backlight light source.
[0209] A white image was displayed on the thus manufactured liquid crystal display device, and visual observation was performed from the front and oblique directions of the display to determine the occurrence of rainbow spots as follows. In addition, the observation angle was set to the angle formed by a line drawn from the center of the display screen in the normal direction (vertical) and a line connecting the center of the display and the position of the eye during observation.
[0210] ◎: No rainbow spots were observed in the observation angle range of 0 to 60 degrees.
[0211] ○: Partially thin rainbow spots were observed in the observation angle range of 0 to 60 degrees.
[0212] ×: Rainbow spots are clearly observed in the observation angle range of 0 to 60 degrees.
[0213] (11) Three-dimensional surface roughness
[0214] Using a stylus three-dimensional roughness meter (SE-3AK, Kosaka Laboratory Ltd.), under the conditions of a needle radius of 2 μm and a load of 30 mg, along the length direction of the film with a cutoff value of 0.25 mm, throughout the measurement length of 1 mm, with a needle feed speed of 0.1 mm / second for measurement, divided into 500 points at a 2 μm spacing, the height of each point is taken into a three-dimensional roughness analyzer (SPA-11). The same operation is performed continuously 150 times at 2 μm intervals in the width direction of the film, that is, 0.3 mm in the width direction of the film is performed, so that the analyzer obtains data. Next, the center plane average roughness (SRa) and the ten-point average surface roughness (SRz) are obtained using an analyzer. It should be noted that the measurement was performed 3 times, and the average value was adopted.
[0215] (12) Haze
[0216] The haze of the film was measured using a turbidity meter (NHD2000, manufactured by NIPPON DENSHOKU INDUSTRIES Co., Ltd.) in accordance with JIS-K7105.
[0217] (13) Inspection of foreign matter in the film
[0218] On the surface of the high Re polarizer protective film side of the manufactured polarizer, place the inspection polarizer in a manner that is orthogonal to the manufactured polarizer in a Nicol state. The polarizer used for inspection is a TAC film with no phase difference on both sides, and a polarizer without damage or foreign matter is selected. In this state, the inspection is carried out using a Nikon universal projector V-12 (projection lens 50x, transmitted illumination beam switching knob 50x, transmitted light inspection). In the case where there are foreign matters in the high Re polarizer protective film, light passes through this part and appears to be shiny. Measure the number of particles with a major diameter of 100 μm or more, particles less than 100 μm and 50 μm or more, and particles less than 50 μm and 20 μm or more in this part, and find the total count of each on the entire surface of the polarizer.
[0219] It should be noted that, when the major diameter cannot be distinguished, the defective portion caused by the foreign matter detected by the above method is cut from the polarizing plate, and the major diameter is determined by observation at a higher magnification using a polarizing microscope. At this time, the high-Re polarizer protective film surface of the polarizing plate is facing upward, and the polarization direction is parallel to the polarization direction of the polarizer on the light source side of the polarizing microscope.
[0220] (14) Amount of antimony atoms in the residue
[0221] After removing the easy-adhesive layer on the surface of the film with a razor, the film was cut into small pieces with scissors. After dissolving 0.1g of the small piece in 20mL of p-chlorophenol / tetrachloroethane mixed solvent = 60 / 40 (weight ratio), a hydrophilic PTFE membrane filter (Advantech Co., Ltd. H010A047A) with an average pore size of 0.1μm was used to filter the dissolved solution using a water flow suction filtration method. After filtration, the filter was recovered, and the residue on the filter was dissolved and constant volume with nitric acid, and it was used as the test solution for determination. In addition, sample preparation was implemented with each sample N = 3. The Sb in the test solution was determined using a high-resolution inductively coupled plasma mass spectrometer (HR-ICP-MS, Thermo Fisher Scientific KK).
[0222] (Production Example 1-Polyester A)
[0223] When the temperature of the esterification reaction tank is raised to 200°C, 86.4 parts by mass of terephthalic acid and 64.6 parts by mass of ethylene glycol are added, and 0.017 parts by mass of antimony trioxide, 0.064 parts by mass of magnesium acetate tetrahydrate, and 0.16 parts by mass of triethylamine as catalysts are added while stirring. Next, the pressure is increased and the temperature is raised. After the pressure esterification reaction is carried out under the conditions of a gauge pressure of 0.34 MPa and 240°C, the esterification reaction tank is returned to normal pressure and 0.014 parts by mass of phosphoric acid is added. Furthermore, the temperature is raised to 260°C in 15 minutes, and 0.012 parts by mass of trimethyl phosphate is added. Then, after 15 minutes, a dispersion treatment is carried out using a high-pressure disperser. After 15 minutes, the obtained esterification reaction product is transferred to a polycondensation reaction kettle and a polycondensation reaction is carried out under reduced pressure at 280°C.
[0224] After the polycondensation reaction was completed, the mixture was filtered with a NASLON filter having a 95% cut diameter of 5 μm, extruded from a nozzle into strands, cooled and solidified using cooling water that had been previously filtered (pore diameter: 1 μm or less), and cut into pellets. The obtained polyethylene terephthalate resin (A) had an intrinsic viscosity of 0.62 dl / g and contained substantially no inactive particles or internal precipitated particles (hereinafter referred to as PET (A)).
[0225] (Production Example 2-Polyester B)
[0226] 10 parts by mass of the dried ultraviolet absorber (2,2'-(1,4-phenylene)bis(4H-3,1-benzoxazin-4-one) and 90 parts by mass of PET (A) (intrinsic viscosity 0.62 dl / g) containing no particles were mixed and a mixing extruder was used to obtain a polyethylene terephthalate resin (B) containing an ultraviolet absorber (hereinafter referred to as PET (B)). It should be noted that a NASLON filter (nominal filtration accuracy 5 μm particles 95% filtration) was set on the melt line for extruding the polyester B into a strand shape for filtering.
[0227] (Manufacturing Example 3 - Preparation of Adhesion-Modified Coating Liquid)
[0228] By carrying out transesterification and polycondensation by a conventional method, a water-dispersible copolyester resin containing a sulfonic acid metal base was prepared, which had a composition of 46 mol% of terephthalic acid, 46 mol% of isophthalic acid and 8 mol% of sodium 5-sulfoisophthalate as dicarboxylic acid components (relative to the total dicarboxylic acid components), and 50 mol% of ethylene glycol and 50 mol% of neopentyl glycol as diol components (relative to the total diol components). Next, 51.4 parts by mass of water, 38 parts by mass of isopropyl alcohol, 5 parts by mass of n-butyl cellosolve, and 0.06 parts by mass of a nonionic surfactant were mixed, and heated and stirred. After reaching 77° C., 5 parts by mass of the water-dispersible copolyester resin containing a sulfonic acid metal base was added, and stirring was continued until the solid of the resin disappeared. The resin aqueous dispersion was cooled to room temperature to obtain a uniform water-dispersible copolyester resin liquid having a solid content concentration of 5.0% by mass. Furthermore, 3 parts by mass of agglomerated silica particles (SYLYSIA310 manufactured by FUJI SILYSIA CHEMICAL LTD.) were dispersed in 50 parts by mass of water, and then 0.54 parts by mass of the aqueous dispersion of SYLYSIA310 was added to 99.46 parts by mass of the aqueous dispersible copolyester resin solution, and 20 parts by mass of water was added while stirring to obtain an adhesive modified coating solution. The coating solution was filtered using a cartridge filter having a 95% separation particle size of 10 μm.
[0229] (Example 1)
[0230] 90 parts by weight of PET (A) resin pellets not containing particles as raw materials for the intermediate layer of the substrate film and 10 parts by weight of PET (B) resin pellets containing an ultraviolet absorber were dried under reduced pressure (1 Torr) at 135°C for 6 hours and then supplied to extruder 2 (for the intermediate layer II). In addition, PET (A) was dried by a conventional method and supplied to extruder 1 (for the outer layer I and the outer layer III) respectively, and dissolved at 285°C. These two polymers were filtered using a filter material of a stainless steel sintered body (nominal filtration accuracy 95% retention of particles of 10 μm), stacked using two types of three-layer confluence blocks, formed into sheets from a joint and extruded, and then wound on a casting drum with a surface temperature of 30°C using an electrostatic casting method and cooled and solidified to produce an unstretched film. At this time, the discharge amount of each extruder was adjusted so that the thickness ratio of the I layer, the II layer, and the III layer was 10:80:10.
[0231] Next, the unstretched PET film was coated on both sides by a reverse roll method in an amount of 0.08 g / m2 after drying. 2 After the adhesive modified coating liquid was applied in the manner of , it was dried at 80° C. for 20 seconds. During the coating, a cartridge filter with a 95% separation particle size of 10 μm was set in the pipeline that sent the coating liquid 1 to the coating die head to remove the aggregates of the particles.
[0232] The unstretched film with the coating layer formed thereon was introduced into a tenter stretching machine, and while holding the end of the film with a clamp, it was guided to a hot air zone at a temperature of 138°C for preheating, and then stretched at a temperature of 90°C and a strain rate of 17.2% / sec in a manner that the film becomes 5.0 times in the width direction. Next, while maintaining the width stretched in the width direction, it was heat treated in a hot air zone at a temperature of 210°C, and then introduced into a hot air zone at a temperature of 160°C, and then subjected to a relaxation treatment of 3% in the width direction, to obtain a uniaxially oriented PET film having a film thickness of about 65 μm.
[0233] It should be noted that in the manufacturing, the difference between the inner diameter of the gasket at the joint part of the flange of the pipe through which the molten resin passes and the inner diameter of the pipe is 50 μm or less. At the start of operation, the resin is discharged three times at a flow rate of 1.2 times the set resin extrusion rate for 5 minutes, and then the film production is started. The film is sampled 30 minutes after the start of production. In addition, the filter element is replaced with a cleaned filter element at the start of operation.
[0234] (Example 2)
[0235] The unstretched film (with a coating layer formed thereon) prepared by the same method as in Example 1 was introduced into a tenter stretching machine, and while holding the end of the film with a clamp, it was guided to a hot air zone at a temperature of 132°C for preheating, and then stretched at a temperature of 90°C and a strain rate of 17.2% / sec in a manner that the film becomes 5.0 times in the width direction. Then, while maintaining the width stretched in the width direction, it was heat treated in a hot air zone at a temperature of 210°C, and then introduced into a hot air zone at a temperature of 160°C, and then subjected to a relaxation treatment of 3% in the width direction, to obtain a uniaxially oriented PET film having a film thickness of about 65 μm.
[0236] (Example 3)
[0237] Except for changing the thickness of the film, an unstretched film (having formed a coating layer) prepared by the same method as in Example 1 was introduced into a tenter stretching machine, and while holding the end of the film with a clamp, it was guided to a hot air zone at a temperature of 130°C for preheating, and then stretched at a temperature of 90°C and a strain rate of 20.0% / sec so that the film became 5.8 times in the width direction. Then, while maintaining the width stretched in the width direction, it was heat treated in a hot air zone at a temperature of 200°C, and then introduced into a hot air zone at a temperature of 140°C, and then relaxed by 3% in the width direction, to obtain a uniaxially oriented PET film having a film thickness of about 40 μm.
[0238] (Example 4)
[0239] Except for changing the thickness of the film, an unstretched film (having formed a coating layer) prepared by the same method as in Example 1 was introduced into a tenter stretching machine, and while holding the end of the film with a clamp, it was guided to a hot air zone at a temperature of 120°C for preheating, and then stretched at a temperature of 102°C and a strain rate of 39.3% / sec in a manner that the film becomes 5.6 times in the width direction. Then, while maintaining the width stretched in the width direction, it was heat treated in a hot air zone at a temperature of 180°C, and then introduced into a hot air zone at a temperature of 160°C, and then relaxed by 3% in the width direction, to obtain a uniaxially oriented PET film having a film thickness of about 50 μm.
[0240] (Example 5)
[0241] Except for changing the thickness of the film, an unstretched film (having formed a coating layer) prepared by the same method as in Example 1 was introduced into a tenter stretching machine, and while holding the end of the film with a clamp, it was guided to a hot air zone at a temperature of 100°C for preheating, and then stretched at a temperature of 90°C and a strain rate of 25.2% / sec so that it became 4.5 times in the width direction. Then, while maintaining the width stretched in the width direction, it was heat treated in a hot air zone at a temperature of 200°C, and then introduced into a hot air zone at a temperature of 160°C, and then relaxed by 3% in the width direction, to obtain a uniaxially oriented PET film having a film thickness of about 60 μm.
[0242] (Comparative Example 1)
[0243] Except for changing the thickness of the film, an unstretched film (having formed a coating layer) prepared by the same method as in Example 1 was introduced into a tenter stretching machine, and while holding the end of the film with a clamp, it was guided to a hot air zone at a temperature of 100°C for preheating, and then stretched at a temperature of 100°C and a strain rate of 34.6% / sec so that the film width in the width direction becomes 5.0 times. Then, while maintaining the width stretched in the width direction, it was heat treated in a hot air zone at a temperature of 180°C, and then introduced into a hot air zone at a temperature of 180°C, and then relaxed by 3% in the width direction, to obtain a uniaxially oriented PET film having a film thickness of about 60 μm.
[0244] (Comparative Example 2)
[0245] A uniaxially oriented PET film having a film thickness of about 65 μm was obtained by the same method as in Example 2 except that the temperature during stretching was 80° C.
[0246] (Comparative Example 3)
[0247] Except for changing the thickness of the film, an unstretched film (having formed a coating layer) prepared by the same method as in Example 1 was introduced into a tenter stretching machine, and while holding the end of the film with a clamp, it was guided to a hot air zone at a temperature of 138°C for preheating, and then stretched at a temperature of 90°C and a strain rate of 49.2% / sec in a manner that the film becomes 5.8 times in the width direction. Then, while maintaining the width stretched in the width direction, it was heat treated in a hot air zone at a temperature of 190°C, and then introduced into a hot air zone at a temperature of 190°C, and then relaxed by 3% in the width direction, to obtain a uniaxially oriented PET film having a film thickness of about 50 μm.
[0248] (Comparative Example 4)
[0249] Except for changing the thickness of the film, an unstretched film (having formed a coating layer) prepared by the same method as in Example 1 was introduced into a tenter stretching machine, and while holding the end of the film with a clamp, it was guided to a hot air zone at a temperature of 115°C for preheating, and then stretched at a temperature of 102°C and a strain rate of 39.3% / sec in a manner that the film becomes 5.6 times in the width direction. Then, while maintaining the width stretched in the width direction, it was heat treated in a hot air zone at a temperature of 180°C, and then introduced into a hot air zone at a temperature of 180°C, and then relaxed by 3% in the width direction, to obtain a uniaxially oriented PET film having a film thickness of about 25 μm.
[0250] (Comparative Example 5)
[0251] Except for changing the thickness of the film, an unstretched film (having formed a coating layer) prepared by the same method as in Example 1 was introduced into a tenter stretching machine, and while holding the end of the film with a clamp, it was guided to a hot air zone at a temperature of 90°C for preheating, and then stretched at a temperature of 90°C and a strain rate of 25.2% / sec so that the film became 4.5 times in the width direction. Then, while maintaining the width stretched in the width direction, it was heat treated in a hot air zone at a temperature of 200°C, and then introduced into a hot air zone at a temperature of 160°C, and then relaxed by 3% in the width direction, to obtain a uniaxially oriented PET film having a film thickness of about 60 μm.
[0252] Table 1 shows the results of measurements on the PET films obtained in Examples and Comparative Examples.
[0253] It should be noted that the amount of fine powder attached to the equipment near the cutting blade after slitting was confirmed. The result showed that the amount of fine powder was small in each example, but a large amount of fine powder was observed in the comparative example. In addition, as a representative, the surface roughness, foreign matter, and haze were measured using the film of Example 1. The results showed that SRa: 2nm or less, SRz: 28nm, haze: 0.7%, the number of foreign matter below 100μm: 0, the number of foreign matter between 50μm and less than 100μm: 0, the number of foreign matter between 20μm and less than 50μm: 1, and the amount of Sb atoms: 2ppm.
[0254] [Table 1]
[0255]
[0256] Industrial Applicability
[0257] According to the present invention, a polyethylene terephthalate resin film having excellent processing adaptability and being particularly capable of effectively suppressing the generation of breakage and convex edges during slitting can be provided. In addition, a polarizing plate, a transparent conductive film, a touch panel, and an image display device such as a liquid crystal display device and an organic EL display device using the polyethylene terephthalate resin film can be provided.
Claims
1. A polyethylene terephthalate resin film, which satisfies the following (1) and (2): (1) The polyethylene terephthalate resin film has a retardation of 3000 to 30000 nm, (2) The mesophase orientation parameter of the polyethylene terephthalate resin film measured by the ATR-FTIR method and represented by the following formula is 0.275 or more, (mesophase orientation parameter) = R slow / R fast in, R slow =(1457cm in the slow axis direction -1 absorbance at 795cm in the slow axis direction) / (absorbance at 795cm in the slow axis direction) -1 Absorbance at fast =(1457cm in the fast axis direction -1 Absorbance at 795cm) / (absorbance at 795cm -1 absorbance at ).
2. The polyethylene terephthalate resin film according to claim 1, further satisfying the following (3) and (4): (3) The elastic modulus in the slow axis direction is 8600 MPa or less, (4) The ratio of the elastic modulus in the slow axis direction to that in the fast axis direction is 3.6 or less.
3. The polyethylene terephthalate resin film according to claim 1 or 2, further satisfying the following (5): (5) The fracture strength in the slow axis direction is 450 MPa or less.
4. The polyethylene terephthalate resin film according to any one of claims 1 to 3, further satisfying the following (6): (6) The rigid amorphous fraction represented by the following formula is 33% by mass or more, (Rigid amorphous fraction (mass %))=100-(Flexible amorphous fraction (mass %))-(Mass fraction crystallinity (mass %)). 5 . A polarizing plate comprising the polyethylene terephthalate resin film according to claim 1 laminated on at least one surface of a polarizer as a polarizer protective film. 6 . An image display device comprising the polarizing plate according to claim 5 .
7. A liquid crystal display device comprising a backlight source, two polarizing plates, and a liquid crystal unit disposed between the two polarizing plates, At least one of the two polarizing plates is the polarizing plate according to claim 5 . An organic EL display device comprising the polarizing plate according to claim 5 . 9 . A transparent conductive film comprising the polyethylene terephthalate resin film according to claim 1 as a base film of the transparent conductive film. 10 . A touch panel comprising the transparent conductive film according to claim 9 . 11 . An image display device comprising the polyethylene terephthalate resin film according to claim 1 as an anti-scattering film or a surface protection film on a visible side of an image display panel.
